A review on phytochemical constituents, role on metabolic diseases, and toxicological assessments of underutilized part of Garcinia mangostana L. fruit - Abdul Rohman, Fitriana Hayyu Arifah, Irnawati&, Gemini Alam, Muchtaridi, Muhammad Rafi (Journal of Applied Pharmaceutical Science, 2020)
Metabolic diseases are one of the problems in public health and become the major causes of mortality. These have led the scientist to solve the metabolic disease-related problems by exploring some natural medicine and phytochemicals to prevent and to treat them. One of the plant medicines potential to be developed is Garcinia mangostana L. or mangosteen which belongs to the family Clusiaceae. The underutilized part of the fruit including pericarp and seed is a promising candidate as herbal medicine, particularly to treat and to prevent the metabolic diseases. This review was aimed to update some research findings regarding the biological activities of the underutilized parts of mangosteen (pericarp and seed) along with phytochemical components. During this review, some information which are relevant to the study have been compiled using scientific literature from electronic search engines, including ScienceDirect, PubMed, Web of Science, Google Scholar, and other scientific electronic resources. Additional literature works were obtained from book chapters, books, websites, government reports, and other related sources. The underutilized part of mangosteen fruit is rich in xanthone derivatives as value-added constituents. The pericarp and seed also contain the derivatives of benzophenones, flavonoids, and anthocyanins. This study highlighted on the possible medicinal properties, especially for metabolic diseases such as obesity and lipid metabolism disorder, high blood pressure, diabetes along with its complication, and cancer. Besides, toxicological assessments were discussed to ensure the safety and trust of the consumers.
Keywords: Garcinia mangostana L., metabolic disease, phytochemistry, toxicological assessment, underutilized part.